Factors Influencing Bronchopulmonary Dysplasia: An Eight-Year Study in a Single Tertiary Care Unit in Thailand - Pallapa Moolmai; Prattana Rattanachamnongk; Buranee Yangthara; Punnanee Wutthigate (Siriraj Medical Journal)
Objective: To assess the incidence trends of severe BPD or death, identify associated risk factors, and develop a predictive model using Jensen’s BPD grading system.